Undescribed Encyrtid Parasites of Homopterous Insects (Hymenoptera: Chalcidoidea). - Mashhood Alam, S. (Contributions to Entomology = Beiträge zur Entomologie, 1961)
There are described as new Aphidencyrtus qadrii and Blastothrix coryli, encyrtid parasites of Homoptera. Revised keys to species of Aphidencyrtus and Blastothrix females are included. Nomenclatural Acts qadrii Mashhood Alam, 1961 (Aphidencyrtus), spec. n. coryli Mashhood Alam, 1961 (Blastothrix), spec. n.